Adverse events associated with Covishield vaccination among healthcare workers in a tertiary hospital in South India. (December 2022) - T Sathyapalan, Dipu; Moni, Merlin; Prasanna, Preetha; Marwaha, Vishal; Bala Madathil, Sai; Edathadathil, Fabia; Jose, Sony A.; Pavithran, Sheela; Muralikrishanan, Rajasree; Ramachandran, Nigith; P R, Roshni; T S, Tinu; et al.
Abstract: Background: Vaccination is the most important prophylactic measure taken to curb COVID-19 pandemics. This study was undertaken to throw light on the safety of Covishield vaccine among health care workers (HCWs) and to assess the co-variates associated with incidence of adverse events. Methods: This prospective observational study was conducted in a tertiary care center in South India as part of the HCW vaccination drive. All consenting HCWs who received the first dose of Covishield vaccine and developed ADRs were included in this study. After vaccination, all beneficiaries were monitored for AEFI for a period of half an hour and later followed up through telephone and google survey forms on day 2 and day 7 of vaccination. The data was subsequently collated into spreadsheet format and analyzed. Results: The study included 1264 consenting healthcare workers who were predominantly youth, aged 15–24 years (n = 583, 46 %) and with a female preponderance of 76 % (n = 960). Past history of COVID-19 infections was reported among 4.6 % (58) of the study population. Postvaccination symptoms were majorly reported during the first (40 %) and second day (44 %) after vaccination with a high prevalence of both local (n = 1083, 85 %) and systemic symptoms (n = 1065, 84 %). The mean duration of symptoms was observed to be 1.4 ± 0.81 days post vaccination. Symptoms were observed significantly high among females (76.7 %, p = 0.013). The prevalence of systemic (88 % vs 80 %) (p < 0.001) and allergic symptoms (7 % vs 3 %; p = 0.03) were observed to be significantly high among respondents with <25 years of age. The systemic and allergic symptoms following vaccination were reported to be low among healthcare workers who had a previous history of COVID-19 infection. Conclusion: COVID vaccination has been observed to be safe and well tolerated with more systemic symptoms reported among younger age group and females.